2011
DOI: 10.1038/ja.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farnesol on mevalonate pathway of Staphylococcus aureus

Abstract: To investigate the mechanism of action by which farnesol functions as an antibacterial agent and inhibits Staphylococcus aureus growth, the growth rates of S. aureus cultured in farnesol versus S. aureus cultured in farnesol and supplemented with 3-hydroxy-3-methylglutaryl (HMG)-CoA or mevalonate were compared. The investigation was designed to observe whether farnesol affected on the mevalonate pathway by using the intermediate metabolites of the pathway. The resulting growth curves demonstrated that mevalona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Kaneko et al . [42] results and ours further provide more evidence that farnesol mechanism of action in S. epidermidis is related with the cell wall membrane integrity. We are currently exploring the role of farnesol in S. epidermidis cell membrane integrity as well as its impact on biofilm physiology.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Kaneko et al . [42] results and ours further provide more evidence that farnesol mechanism of action in S. epidermidis is related with the cell wall membrane integrity. We are currently exploring the role of farnesol in S. epidermidis cell membrane integrity as well as its impact on biofilm physiology.…”
Section: Discussionsupporting
confidence: 76%
“…While S. epidermidis biofilms have been proposed to partially detach fragments of the biofilm [6] in order to potentially colonize other regions of the host, cell detachment is not yet fully understood, however some genetic regulation might be involved [41]. Recently Kaneko et al showed that farnesol interfered with the S. aureus mevalonate pathway, which is related with cell membrane maintenance and protein anchoring, among other important cell functions [42]. S. aureus biofilm production and metabolism is similar to S. epidermidis [43].…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrated that at high concentrations, farnesol triggers a process of apoptosis in C. albicans and in human oral squamous carcinoma cells, which was preceded by ROS production in both eukaryotic cells (39)(40)(41). In S. aureus, several possibilities for farnesol's mechanism of killing have been proposed, including disruption of cell membrane integrity and leakage of K ϩ ions (38,(42)(43)(44). Therefore, given its toxicity, previous studies focused primarily on exploring the potential of exogenous farnesol as an antimicrobial agent.…”
Section: Figmentioning
confidence: 78%
“…26, 28, 29 Although free nanoparticles are devoid of antibacterial activity against S. mutans , either in planktonic phase or in biofilms (Figure 4), nanoparticle-mediated delivery may facilitate farnesol incorporation into bacterial membranes due to localized release. Whether nanoparticles enhance the ability of farnesol to disrupt membrane integrity 26, 28, 29, 66, 68, 72 or increase intracellular drug accumulation 73 awaits further mechanistic investigations.…”
Section: Resultsmentioning
confidence: 99%